Research on Obstacles and Optimization Paths of Emotional Connection Between Virtual Anchors and Consumers - Lin, Yurui; Liu, Xiaowen; Liu, Wanzhao (International Journal of Multidisciplinary Research, 2025)
With the deep integration of artificial intelligence and virtual reality technology, virtual anchors have become an important media form in e-commerce platforms, news communication, and other fields. This article systematically analyzes the three core obstacles of technology, cognition, and operation in the emotional connection between virtual anchors and consumers, as well as the deep-seated causes. The research found that the rigid human-computer interaction at the technical level stems from the ceiling of motion capture simulation technology, the lack of trust at the cognitive level is rooted in the perception of emotional commodification, and the homogenization at the operational level is attributed to security dependence; the three-dimensional optimization path can effectively solve the above obstacles by strengthening sensory immersion, balancing real perception. This research addresses fragmented studies and offers theoretical and practical support for the industry’s sustainable, high-quality development.